In vivo Biocompatibility and Bioactivity of Calcium Silicate-Based Bioceramics in Endodontics - Song, Wencheng; Sun, Wei; Chen, Lili; Yuan, Zhenglin (Frontiers in Bioengineering and Biotechnology, 2020)
Endodontic therapy is aimed to preserve or repair the activity and function of pulp and periapical tissues. Due to the excellent biological features, a substantial number of calcium silicate-based bioceramics have been introduced into the endodontics and simultaneously increased the success rate of endodontic treatment. In addition, the update of these calcium silicate-based biomaterials promotes the advancement of endodontics. Especially, the studies about the in vivo biocompatibility and bioactivity of calcium silicate-based bioceramics contribute greatly to development of other novel endodontics application. The creation of appropriate animal models could mimic the pathophysiological changes of different endodontic diseases in the presence of these calcium silicate-based bioceramics, which could help us understand the in vivo biocompatibility and bioactivity of calcium silicate-based bioceramics when used in endodontics. Therefore, the present review will focus on the in vivo biocompatibility and bioactivity of calcium silicate-based bioceramics in endodontics.